2015
DOI: 10.26848/rbgf.v8.2.p365-376
|View full text |Cite
|
Sign up to set email alerts
|

Medição e Simulação dos Fluxos de Energia e Evapotranspiração em Solo Cultivado com Brachiaria decumbens na Microrregião de Garanhuns – PE

Abstract: O cultivo de pastagem no Estado de Pernambuco destaca-se como a principal fonte de alimentação do rebanho bovino da região. Não sendo diferente das demais culturas, o conhecimento da quantidade de água requerida pela pastagem em cada fase de seu desenvolvimento é fator importante para o sucesso produtivo da lavoura. Dessa forma, o objetivo do presente estudo foi medir e simular a evapotranspiração da Brachiaria decumbens cultivada em sequeiro na microrregião de Garanhuns – PE, empregando os métodos do balanço … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…These authors found mean values of 2.27; 0.24 and 10.49 for n, m, and η, respectively, for sandy loam soils. Gomes et al (2015) evaluated the hydrodynamics parameters of sandy soil, obtaining similar values to this study (n=2.50; m=0.17 and η=10.71). Lassabatère et al (2006) and Santos et al (2012a), who analyzed the n, m, and η parameters for different textural classes, emphasize that the values of n e m are commonly higher in coarse soils like the sandy soils than in fine soils.…”
Section: Gcm -3 ] ------[%] -------------[-] -----------mentioning
confidence: 53%
“…These authors found mean values of 2.27; 0.24 and 10.49 for n, m, and η, respectively, for sandy loam soils. Gomes et al (2015) evaluated the hydrodynamics parameters of sandy soil, obtaining similar values to this study (n=2.50; m=0.17 and η=10.71). Lassabatère et al (2006) and Santos et al (2012a), who analyzed the n, m, and η parameters for different textural classes, emphasize that the values of n e m are commonly higher in coarse soils like the sandy soils than in fine soils.…”
Section: Gcm -3 ] ------[%] -------------[-] -----------mentioning
confidence: 53%